Ways to effectively organize control of the oil and gas, fuel energy industry through taxes - Abdullaev Shuxrat Sultanbaevich (Genius Journals, 2024)
In the case of processing of extracted natural gas, oil and gas condensate in this article, realization and expansion of the tax base of products obtained from these minerals, effective organization of tax control in large taxpayers in the field of oil, gas, fuel energy industry issues and scientific proposals and recommendations for solving the problem of taxation have been developed.
Keywords: source of income; tax administration; tax reporting